2015
DOI: 10.1108/lht-08-2014-0077
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy of vendor-supplied accessibility documentation

Abstract: Structured Abstract:Purpose: In an effort to ensure vendor compliance with Section 508, some libraries have begun requesting Voluntary Product Accessibility Templates (VPATs) or other documentation of accessibility compliance. The purpose of this paper is to assess the accuracy of vendor-supplied compliance documentation, and to identify common accessibility issues highlighted by the VPATs. A detailed discussion of vendor responses to each Section 508 checkpoint is provided in the Appendix. Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…As DeLancey reported, VPATs can incorrectly be filled out by a vendor and is a claim of performance, although many vendors are starting to back up VPATs with accessibility testing. 12 Basically, librarians are considering whether a product complies with these levels to be fully compliant.…”
Section: Csi Library's Vpat Projectmentioning
confidence: 99%
“…As DeLancey reported, VPATs can incorrectly be filled out by a vendor and is a claim of performance, although many vendors are starting to back up VPATs with accessibility testing. 12 Basically, librarians are considering whether a product complies with these levels to be fully compliant.…”
Section: Csi Library's Vpat Projectmentioning
confidence: 99%
“…Another interesting area of focus has been the incorporation of accessibility into collection development policies as a mean of using our purchasing power to pressurize vendors into prioritizing accessibility (Dermody and Majekodunmi, 2011; Schmetzke, 2015; Ostergaard, 2015; Delancey and Ostergaard, 2016). Asking vendors to disclose their accessibility policies during the procurement process has become routine at some institutions, often by means of requesting a voluntary product accessibility template (VPAT), a government-created aid to help people buy institutions purchase products that meet Section 508 standards (Wakimoto and Soules, 2011; Billingham, 2014; Blechner, 2015; DeLancey, 2015; Falloon, 2015; Ostergaard, 2015; Riley-Huff, 2015; Delancey and Ostergaard, 2016; Mune and Agee, 2016; Ng, 2017). This has the potential to influence vendors to prioritize accessibility.…”
Section: Achieving Accessibilitymentioning
confidence: 99%
“…The study found that, when compared to the accessibility tests, the vendor-supplied information was inaccurate 19.6% of the time. 8 As usability testing was beyond the scope of the ERM Unit's inventory, the existence of a VPAT was considered a positive indicator of accessibility.…”
Section: Compiling the Accessibility Inventorymentioning
confidence: 99%